Women Aesthetic as A Source of Appetence and Pleasure in Qubadi Jalizada’s Poems - Yadgar Rasool Balaky; Rzgar Umer Fattah (Zanco Journal of Humanity Sciences)
This study which is titled “Women Aesthetic as A Source of Appetence and Pleasure in Qubadi Jalizada’s Poems” is a great effort to get familiar with the women aesthetic in general, and with the appetence, pleasure and women’s esthetics in Jalizad’s poems in particular. It is also an essential method to gain insight into the proficiency, ability, sense, esthetic codes and perspectives of the poet in this respect.